ESP Students’ Self-Reflection on English Speaking Anxiety: An Investigation on Gender’s Perspectives - Muhamad Nova (SAGA: Journal of English Language Teaching and Applied Linguistics, 2024)
Speaking in a foreign language becomes a challenge for many students, including ESP students. In ESP class, the students learn English for specific context related to the professional fields. Thus, having anxiety in the English class could affect their future performance in their future job. The current study seeks for insight on identifying speaking anxiety awareness among ESP students through self-reflection. The students are required to describe on of the tourist attraction in front of the class and have a self-reflection on their performance. With the total of 15 male and 15 female students, the study applied a qualitative study with case study design. The data were collected through classroom observation, questionnaires, and interview. The data were triangulated and analyzed through data condensation, data display, and conclusion drawing. As a result, the male students tend to have speaking anxiety than the female students. Based on the male students’ perceptions, pronunciation difficulty, lack of grammar comprehension, lack of vocabulary mastery, and lack of confidence become the cause of the speaking anxiety, while the female students have lack of practice, nervousness, and pronunciation difficulty as the problem. Thus, it is suggested the English lecturer to provide more practice on language system, such as grammar, vocabulary, and pronunciation to shape students’ comprehensibility on English. Also, the ESP students need to have extensive speaking practice to boost their confidence in speaking in front of the class.